Humor in classroom / Azmi Abdul Latif - Abdul Latif, Azmi (Akademi Pengajian Bahasa, 2021)
A research by Ziyaeemehr, Kumar and Abdullah (2011) discovered that there was a tendency among Malaysian educators to avoid using humor in their ESL classrooms. Among the reasons given were humor was not part of their personality, they lack competence to be humorous and they were syllabus oriented. This is in contrast to Morreall (2007) who has championed the use of humor because when ‘you utilize humor, you get people's attention, you relax them, get them into a good mood, and more receptive to your message’. Having taught ESL/EFL for the past twenty over years, the speaker found that humour has helped to motivate his students. His PhD research on the use of parody in EFL class revealed that the students’ critical thinking and writing proficiency improved significantly after undergoing parodyintegrated language activities. In this workshop, the speaker will share some tips on how to use humour in English language classroom.